Environmental Factors Associated with the Occurrence of Filariasis in Asahan Regency, North Sumatra Province - Ismili, Israyani; Sri Malem Indirawati; Lubis , Zulkifli (TALENTA Publisher, Universitas Sumatera Utara, 2024)
Filariasis is a serious parasitic infection caused by thread-like worms known as filariae. These worms are transmitted to humans through the bites of infected mosquitoes. The infection mainly affects the lymphatic system, which is part of your body's immune system. Poor sanitation and lack of proper housing infrastructure are a few aspects causing filariasis. This research aims to to determine the environmental factors related to the incidence of filariasis in Asahan Regency, North Sumatra Province Data was collected using a purposive sampling technique and involved direct observation of the research subjects. This data was analyzed using univariate and bivariate analysis to test the hypothesis and using numerous variables like temperature, humidity, conditions around the house that become mosquito habitat. This paper found that the majority of respondents with filariasis had non-permanent walls, ceilings, and no mosquito mesh in their homes. Houses with non-permanent walls or without mosquito mesh were found to have a higher risk of filariasis. Specifically, non-permanent walls increased the risk by 4.342 times, and the absence of mosquito mesh increased the risk by 4.848 times. The condition of the ceiling was not proven to be a risk factor for the occurrence of filariasis. The presence of mosquito mesh was found to be an effective preventive measure in reducing the risk of human contact with the filariasis vector mosquitoes.